Optimization of FPSO Glen Lyon Mooring Lines - Figueiredo, Paulo Alexandre Rodrigues de Vasconcelos (2019)
During oil and gas inspection and extraction operations both in deep and ultra-deep water, vessel mooring is a very important factor for the development of oil fields. For these depths, standard stand-alone surface facilities e.g. jack up rigs or offshore fixed platforms are not suitable due to the harsh collinear and non-collinear environment in-situ (location, waves, surface and underwater current, sea tides, ice, etc.). For deep sea wells clusters, it is usual to use floating production storage offloading (FPSO) as surface platforms for long time exploitation periods. Subsea expenditure, refers the cost of the subsea project and generally includes the capital expenditures (capex) and operational expenditures (opex). In the production of hydrocarbons capex and opex exponentially increases with increasing depth, resulting in a need for precise detailed design phase for analysis of systems to verify components strength, ductility and fatigue, stiffness, instabilities, corrosion etc. The design of oilfields is most of the times overrated (in a very conservative way) due to several requirements and complex models of costs evaluation. After detailed phase and installation of all facilities and components, as well as due to the expected life design for hydrocarbons exploitation all anchoring system shall withstand the environmental loads in order to not compromise the operation. Each oilfield has a unique development, since environmental phenomena are unique in each earth location. This work refers to the optimization process of an anchoring system for deep waters in the Schiehallion Field, or in other words, the complete development of the mooring system for a FPSO, from the positioning in-situ with environmental conditions and vessel characteristics (Orcaflex), further optimization of the mooring system for an equivalent system (Matlab), mechanical design of the mooring system (CATIA), structural detailed analysis (Altair and Nastran) as fatigue life analysis. In order to reproduce all the mooring process, it is performed and initial comparison of the former FPSO (Schiehallion FPSO) that has been working in-situ since 1993 till its replacement for the new vessel (Glen Lyon FPSO). Due to the latest discoveries in the oilfield, the project has to be redesigned alongside with former wells and having in consideration recent discovered wells. Further optimization of the complete fixation system was verified as well as finally detailed structural analysis of specific components in key locations with higher margin of failure. Within this work, all the methodology which led to the optimization of Glen Lyon mooring lines was fully detailed from vessel analysis to detailed mooring mechanical design, constraints and requirements were applied, trade-offs and assumptions made during this critical development phase are presented and discussed.